Beyond green or tech: Cultivating entrepreneurial ecosystems for the twin transition - Jaime Joel Rodriguez Santiago (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
The 'twin transition' concept underscores the interconnectedness of digitalization and sustainability - two major transformative processes shaping our world. While these transitions have often been viewed separately, their interdependence and mutual reinforcement are increasingly recognized. Entrepreneurs are uniquely positioned to drive progress at the intersection of these twin transitions, as innovative actors capable of developing solutions that seamlessly integrate digital technologies and sustainable approaches. Within the entrepreneurial ecosystem domain, two bodies of literature have emerged - one focused on digital entrepreneurship and the other on sustainability-oriented entrepreneurship. Though these streams have developed in parallel, they remain largely siloed. This paper first analyzes the interplay between digital transformation and sustainability transitions, highlighting their synergies and tensions. Building on this foundation, the paper introduces a conceptual framework that outlines key dimensions for cultivating entrepreneurial ecosystems capable of leveraging the opportunities offered by both transitions. This framework provides a roadmap for policymakers, entrepreneurs, and ecosystem actors interested in creating an environment that contributes to a sustainable planet in a digital age.
Keywords: L26; M13; Q56; 330; Entrepreneurial ecosystems; Twin Transition; Sustainability; Digitalization; Sustainable Transitions; Digital Transformation